G-Protein biased opioid agonists: 3-hydroxy-N-phenethyl-5-phenylmorphans with three-carbon chain substituents at C9. Issue 8 (24th June 2020) - Gutman, Eugene S.; Bow, Eric; Li, Fuying; Sulima, Agnieszka; Kaska, Sophia; Crowley, Rachel; Prisinzano, Thomas E.; Lee, Yong-Sok; Hassan, Sergio A.; Imler, Gregory H.; Deschamps, Jeffrey R.; Jacobson, Arthur E.; et al.
Abstract : Three C9 substituted N -phenethyl-5-phenylmorphans were found to be extremely G-protein biased potent mu opioid receptor partial agonists that did not recruit beta-arrestin at all in both the PathHunter assay and in the Tango assay. Abstract : A series of compounds have been synthesized with a variety of substituents based on a three-carbon chain at the C9-position of 3-hydroxy- N -phenethyl-5-phenylmorphan (3-(2-phenethyl-2-azabicyclo[3.3.1]nonan-5-yl)phenol). Three of these were found to be μ-opioid receptor agonists in the inhibition of forskolin-induced cAMP accumulation assay and they did not recruit β-arrestin at all in the PathHunter assay and in the Tango assay. Compound 12 (3-((1 S, 5 R, 9 R )-2-phenethyl-9-propyl-2-azabicyclo[3.3.1]nonan-5-yl)phenol), 13 (3-((1 S, 5 R, 9 R )-9-(( E )-3-hydroxyprop-1-en-1-yl)-2-phenethyl-2-azabicyclo[3.3.1]nonan-5-yl)phenol), and 15a (3-((1 S, 5 R, 9 R )-9-(2-hydroxypropyl)-2-phenethyl-2-azabicyclo[3.3.1]nonan-5-yl)phenol) were partial μ-agonists. Two of them had moderate efficacies ( E MAX ca. 65%) and one had lower efficacy, and they were ca. 5, 3, and 4 times more potent, respectively, than morphine in vitro . Computer simulations were carried out to provide a molecular basis for the high bias ratios of the C9-substituted 5-phenylmorphans toward G-protein activation.